A case of De Garengeot hernia requiring early surgery. (21st July 2015) - Pan, Chao-Wen; Tsao, Min-Jen; Su, Ming-Shan
Abstract : De Garengeot hernia is a rare clinical entity defined as the presence of a vermiform appendix within a femoral hernia sac. A 50-year-old woman presented to the emergency department with a painful lump over her right groin region. A bedside ultrasound was performed and soft tissue lesion was suspected. CT was performed and revealed a swollen tubular structure with fat stranding within the mass. De Garengeot hernia with acute appendicitis was diagnosed preoperatively, and an emergency appendectomy and hernioplasty were performed. Although it is usually an incidental finding during hernioplasty, De Garengeot hernia should be considered in the differential diagnosis of patients with an incarcerated femoral hernia. Mesh repair can be performed depending on the clinical situation. We report a rare case of incarcerated femoral hernia with acute appendicitis that required early surgical management to avoid associated complications.